2014
DOI: 10.1097/01.xeb.0000455203.78034.46
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing emotional labor of clinical nurses in a university hospital

Abstract: data, physical risk factors, job strain, work-related musculoskeletal symptoms, health and safety education, and health behaviors related to musculoskeletal problems. Data were analyzed using STATA 12.0 program. Results: 1) General characteristics of subjects were as follows; all 96 subjects were female and their mean age was 33.8 AE 5.5 years. Subjects' average height was 161.4 AE 4.5 cm, average weight was 52.6 AE 4.3 kg, and average work experience in echocardiography lab was 84.1 AE 5.8 months. 2) Accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Educating nurses about the attribution process may increase their awareness of the way their perceive patients, thereby helping them control their emotional labour. personal characteristics, research has shown that age, gender, intelligence (Johnson & Spector 2007, Hur et al 2014, personality traits (Liu et al 2010, Wegge et al 2010, Biron & van Veldhoven 2012, Choi et al 2014, affectivity (Judge et al 2009, Diefendorff et al 2011, Kammeyer-Mueller et al 2013 and personal life experiences (Montgomery et al 2006) might affect how one manages emotions; the most influential organizational factors in this regard were shown to be work attitudes (Grandey 2003, Gosserand & Diefendorff 2005, Allen et al 2010) and job demands (Brotheridge & Lee 2002, Cheng et al 2013, Su 2013. Recent research on nurse-patient interaction-related factors has shown nurses' surface acting being related to frequent encounters with patients (Diefendorff & Greguras 2009, Su 2013 and to patients' disrespect for nurses (Diefendorff et al 2011, Choi et al 2014.…”
Section: What Are the Key Findings?mentioning
confidence: 99%
See 1 more Smart Citation
“…Educating nurses about the attribution process may increase their awareness of the way their perceive patients, thereby helping them control their emotional labour. personal characteristics, research has shown that age, gender, intelligence (Johnson & Spector 2007, Hur et al 2014, personality traits (Liu et al 2010, Wegge et al 2010, Biron & van Veldhoven 2012, Choi et al 2014, affectivity (Judge et al 2009, Diefendorff et al 2011, Kammeyer-Mueller et al 2013 and personal life experiences (Montgomery et al 2006) might affect how one manages emotions; the most influential organizational factors in this regard were shown to be work attitudes (Grandey 2003, Gosserand & Diefendorff 2005, Allen et al 2010) and job demands (Brotheridge & Lee 2002, Cheng et al 2013, Su 2013. Recent research on nurse-patient interaction-related factors has shown nurses' surface acting being related to frequent encounters with patients (Diefendorff & Greguras 2009, Su 2013 and to patients' disrespect for nurses (Diefendorff et al 2011, Choi et al 2014.…”
Section: What Are the Key Findings?mentioning
confidence: 99%
“…The possibility that the same service provider might practice different emotional labour strategies on different occasions has been overlooked. Only recently has research begun exploring the possibility that particular emotional labour strategies might be triggered by patient-provider interaction (Simbula 2010, Biron & van Veldhoven 2012, Choi et al 2014. The current study aims to further this direction of enquiry, by addressing the question of whether nurses' emotional labour strategies vary across encounters with patients due to their perceptions of patients' attributes.…”
Section: Introductionmentioning
confidence: 99%